The design of a web-based application tracer study at SMK Kesehatan Surabaya - Mardiyah, Dewi Rahayu; Nurcahyawati, Vivine; Erstiawan, Martinus Sony (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
SMK Kesehatan Surabaya is a vocational school that has two majors, which is nursing and pharmacy. Tracer study is one of elements of accreditation and used to determine academic policies especially in the preparation of the curriculum. Tracer study process in SMK Kesehatan Surabaya currently experiencing some problems, namely the questionnaire format that less informative, there has been no feedback from the graduate user and alumni, there has been no details data of graduate user, alumni data is less valid, data collection takes a long time and repeatedly, and the issue of data security is not guaranteed. The solution that can solve the problem is making tracer study applications to facilitate the implementation of tracer study, so data collection of alumni more accurate and quicker than before, there is feedback from the graduate user and alumni, as well as there is a report tracer study that used the stages of Software Development Life Cycle (SDLC) which includes the step of system analysis, system design and system implementation. The result showed that based on testing, application that have been made can help in obtaining feedback from users graduates and the alumni and generate report the tracer study of tables and charts that will facilitate the SMK in determining policy, and as a reference to repair curriculum to improve the quality of alumni in the future.